Coupling of Nickel Boride and Ni(OH)2 Nanosheets with Hierarchical Interconnected Conductive Porous Structure Synergizes the Oxygen Evolution Reaction. Issue 20 (13th September 2018) - Liang, Xiaoguang; Dong, Ruoting; Li, Dapan; Bu, Xiuming; Li, Fangzhou; Shu, Lei; Wei, Renjie; Ho, Johnny C.
Abstract: Earth‐abundant and highly‐efficient electrocatalysts for oxygen evolution reaction (OER) are urgently desired to realize the large‐scale storage and conversion of renewable energies. In this work, we develop a hierarchical porous electrocatalyst structure utilizing Ni(OH)2 nanosheets directly synthesized on Ni foam as the conductive and interconnected supports. By coupling with amorphous Ni−B nanoparticles, this hybrid catalyst exhibits dramatically enhanced electrocatalytic activities and durabilities towards OER. In specific, along with the optimized Ni−B loading, this catalyst requires only an impressively small overpotential of 300 mV to drive a current density of 100 mA cm −2 for oxygen evolution in 1 M KOH electrolyte. Meanwhile, it also yields a small Tafel slope of 49 mV dec −1 and a superior long‐term stability. All these results evidently indicate that the hierarchical hybridization of Ni−B with Ni(OH)2 on Ni foam can effectively synergize the oxygen evolution, opening up a new vista for designing high‐performance transition metal‐based nanostructures in the field of electrochemical water splitting. Abstract : A hierarchical porous electrocatalyst structure utilizing Ni(OH)2 nanosheets directly synthesized on Ni foam as the conductive and interconnected supports is developed for the deposition of Ni−B nanoparticles by using the facile dip‐coating method. This synergistic hybrid electrocatalyst system configured of Ni−B nanoparticles, Ni(OH)2 nanosheets and Ni foam can exhibit dramatically electrocatalytic activities and superior long‐term stabilities towards oxygen evolution reaction.